Eating and Reading Hiromi Goto - Harris, Lisa (Cuizine)

(untitled) (McGill University Library, 2008)
AbstractHiromi Goto uses salted sour plums, cucumber and tonkatsu to expose the limits of reading and eating as ways of knowing gender and race. Ultimately, Goto argues, "difference exists, all cannot be understood." The narrator of Goto’s fictocriticism, Not Your Ethnic Body, describes herself through food to challenge how the female Japanese-Canadian body is consumed through writing. Yet she makes herself unpalatable to readers by prompting them to recoil and, thereby, to question their own reading practice.Goto rarely provides secure ideological footing in her prose; although there is space to gender or racialize her characters, she never confirms the legitimacy of such assumptions. The narrator of The Kappa Child is ambiguously gendered, for example, and has an ambivalent relationship to cucumbers. The family meal in Chorus of Mushrooms interrupts food’s conciliatory role in multicultural exchange. Goto’s work demonstrates that culinary authenticity, when tied to a particular place or racial identity, is always socially constructed and subject to change.